Instructional Leadership, Pedagogical Competence, and School Culture: Determinants of Learning Quality in Public Junior High Schools in Rembang District - Nuraini, Nuraini; Haryati, Titik; Sumarno, Sumarno (Journal of Educational Sciences, 2025)
Improving learning quality in secondary education requires the integration of multiple factors, including school leadership, teacher competence, and organizational culture. In non-urban areas such as Rembang District, public junior high schools often face challenges in maximizing these aspects to achieve effective teaching and learning outcomes. This study aims to analyze the influence of principal instructional leadership, teachers’ pedagogical competence, and school quality culture on learning quality in public junior high schools in Rembang District. Using a quantitative survey approach, data were collected from 145 teachers through a validated and reliable Likert-scale questionnaire, and analyzed using simple and multiple linear regression techniques. The results indicate that all three variables have a positive and significant effect on learning quality, both individually and collectively, with school quality culture being the most dominant factor. Together, the variables explain 94.4% of the variance in learning quality. These findings underscore the importance of synergy among leadership, competence, and culture in improving learning outcomes and provide strategic insights for school-based policy development.